Biblioteca universitária como ator ativo na divulgação científica por meio da ação cultural - Demarchi, Alini Cristiani De Carli (2021)
Scientific dissemination includes the transmission of scientific knowledge produced in educational and research institutions, for society, especially for non-specialist citizens. In this perspective, university libraries can play a fundamental role looking for ways to present the potential of science as an element of social transformation. The objective of this research was to investigate the performance of the university library, as an active actor in scientific dissemination, through cultural action. The research method used was ex post facto. The units of analysis were the Community Library of UFSCar and the National Institute of Science and Technology of Hymenoptera Parasitoids (INCT Hympar). It was possible to achieve the following results:1] identification of cultural practices and initiatives, involving scientific dissemination to non-specialist citizens; 2] identification of benefits for the library, for the research group and for society. It is considered that through cultural initiatives, multicentric Brazilian research centers, through university libraries, can have a closer relationship with society, promoting the appropriation of scientific and technological knowledge by the lay citizen, through scientific dissemination.